Potential of using palm oil fuel ash and expanded polystyrene as an alternative concrete substance - Osman, Mohamad Hairi; Adnan, Suraya Hani; Yahya, Nur Faezah (Penerbit UTHM, 2020)
Recently, the use of recyclable materials as concrete materials has become increasingly popular. Many researchers have interested on the use of different materials such as fibre, pozzolanic materials, plastic, polystyrene, food waste and so on for the replacement of cement, fine and coarse aggregates, as well as sand. This is because the disposal of industrial waste and non-biodegradable materials such as plastic or polystyrene has increased drastically in recent years, thereby causing many problems to the environment. In addition, the palm oil industry has also been contributing to the increasing amount of industrial waste. Previous studies have identified the potential of palm oil fly ash (POFA) and expanded polystyrene (EPS) as concrete substances. The purpose of this study was to determine the compressive strength, density and thermal conductivity of concrete made using partial percentages of POFA and EPS as cement and fine aggregate replacement, respectively. The proportions of POFA used as a cement replacement were 10%, 20%, 30% and 40% by weight. Meanwhile, the proportions of EPS used as fine aggregate replacement were 10%, 20% and 30% by volume. The mechanical properties between concrete containing POFA and EPS and that of normal concrete were compared. The concrete samples were designed to achieve the target strength of 25 MPa at the age of 28 days. Through this study, the higher proportions of POFA and EPS used showed the lower compressive strength and density of concrete. The optimum percentages for cement and fine aggregate replacement were determined as 20% of EPS and 20% of POFA, respectively. The concrete compressive strength containing 20% of EPS and 20% of POFA closely achieved the strength of 20 MPa which is the highest compressive strength at 28 days compared to other percentages of replacement and fulfilled the requirements strength of structural concrete. Through this study also, showed the decrease in thermal conductivity was mainly contributed by the volume of EPS used. The lower thermal conductivity occurred due to EPS particles characteristic which is lower thermal capacity.